Saifiddin Bokharzi - A Thug Who Developed The Teaching Of Kubravia - Fayzulloyevna, Norova (Buletin Antropologi Indonesia, 2025)
In this article, the teaching of Najmuddin Kubro, who is the representative of Kubravian teachings of Saifiddin Boharzi, and his relationship with him are highlighted. Also, the article describes the details of chilling in the works of Saifiddin Boharzi "Voqeoti khilvat". it describes what he saw in Khilvat based on the assignments of his teacher Najmiddin Kubro.